A pedunculated esophageal chondromatous hamartoma in a child - Dan-Alexandru Iozsa; Maria Puscasu; Catalin Gabriel Cirstoveanu; Vlad Denis Constantin; Anca Silvia Dumitriu; Stana Paunica; Nicolae Sebastian Ionescu (Journal of Mind and Medical Sciences)
Esophageal tumors are uncommon in pediatric population and most of them are benign. Esophageal hamartomas have been reported extremely rare in children. These can present as intramural tumors of the esophageal wall or as polyps. Dysphagia is the main symptom described in their case, but other specific symptoms are also reported. Such symptoms encountered in clinical practice are represented by obstructive apnea episodes and bradycardia, poor weight gain, epigastric or retrosternal pain, hematemesis or melena, dysphonia or tracheal sounds. Diagnosis can be delayed due to the insidious onset and non-specific symptoms, therefore patient’s compliance to follow-up and broad, careful evaluation are mandatory. Preoperative imagistic assessment is extremely important for a precise definition of the tumor’s anatomical relations, especially when facing large tumors located in the posterior mediastinum. Herein we report a case of a large chondromatous polypoid hamartoma of the esophagus in a 9 years old boy, emphasizing over the diagnosis and surgical challenges we have met, along with comments on illustrative similar cases reported in the literature.